The Effect of Corporate Social Responsibility Disclosure on the Performance of Islamic Banks in Indonesia - Aula, Rahmiatul; Sumiyati, Sumiyati; Mai, Muhammad Umar (Universitas Muhammadiyah Yogyakarta, 2022)
Research aims: This study intends to inspect the effect of Corporate Social Responsibility Disclosure (CSRD) on performance. CSRD was divided into CSRD-All, CSRD-Economic, CSRD-Environment, and CSRD-Social variables. Performance was proxied by the variables ROA and ROE.Design/Methodology/Approach: The research model was built in path analysis and processed using the Wrap-PLS application.Research findings: The analysis results indicated that CSRD tended to be strongly associated with higher bank performance. It was indicated by a significant positive effect of CSRD-All on ROA and ROE. In addition, it was indicated by the significant positive effect of CSRD-Economic and CSRD-Environment on ROA. This study's results contribute to financial literature, particularly the causal relationship between CSRD and Indonesian Sharia Commercial Banks' performance.Theoretical contribution/ Originality: The study results provide insight and input for the management of Islamic Commercial Banks concerning CSRD activities and performance.Practitioner/Policy implication: The results of this study are supposed to be useful as directions for stakeholders in deciding their investment in Indonesian Sharia Commercial Bank shares.Research limitation/Implication: This research only used CSRD, ROA, and ROE.